PRACTICES OF VEGETABLE FARMERS TO FACE CLIMATE CHANGE IN IRAQ / CASE STUDY IN BAGHDAD AND BABYLON PROVINCES - Rakhit, Mahdi; Lafta, Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The study was aimed to identify the reality of vegetable farmers practices to face climate change in Iraq in general and in each field of research. To achieve the objectives, a questionnaire consisting of (75) items distribute  over (3) areas are designed, after completing its design procedures in terms of validity and reliability, it is presented to a stratified random sample of (128) vegetable farmers in the reality of (82) farms from Baghdad province  and (46) farms from Babylon province, the data are collected and then analyze using the social statistical analysis program (SPSS), The research results have show the practices of vegetable farmers to face climate change were of medium importance, as all areas of planting vegetables to face climate changes in a weighted range of (1.93-1.68), which is lower than the hypothetical average of (2) degrees, With a percentage weight between (64.33 - 56%), the research recommended the need to intensify extension and preparation efforts to enable vegetable farmers to face climate change.